A SIX1/EYA2 small molecule inhibitor disrupts EMT and metastasis - Zhou, Hengbo (Cancer Res, 2020)
Metastasis is the major cause of mortality for cancer patients, and dysregulation of developmental signaling pathways can significantly contribute to the metastatic process. The SIX1/EYA transcriptional complex plays a critical role in the development of multiple organs and is typically downregulated after development is complete. In breast cancer, aberrant expression of SIX1 has been demonstrated to stimulate metastasis through activation of TGF-β signaling and subsequent induction of epithelial-mesenchymal transition (EMT). In addition, SIX1 can induce metastasis via non-cell autonomous means, including activation of GLI-signaling in neighboring tumor cells and activation of VEGF-C-induced lymphangiogenesis. Thus, targeting SIX1 would be expected to inhibit metastasis while conferring limited side effects. However, transcription factors are notoriously difficult to target, and thus novel approaches to inhibit their action must be taken. Here we identified a novel small molecule compound, NCGC00378430 (abbreviated as 8430), that reduces the SIX1/EYA2 interaction. 8430 partially reversed transcriptional and metabolic profiles mediated by SIX1 overexpression and reversed SIX1-induced TGF-β signaling and EMT. 8430 was well tolerated when delivered to mice and significantly suppressed breast cancer-associated metastasis in vivo without significantly altering primary tumor growth. Thus, we have demonstrated for the first time that pharmacological inhibition of the SIX1/EYA2 complex and associated phenotypes is sufficient to suppress breast cancer metastasis.